Selective liquid-phase hydrogenation of furfural to furfuryl alcohol over Cu-based catalysts - Villaverde, María Magdalena (2013)
In this work, the liquid-phase furfural hydrogenation over different Cu-based catalysts was studied. The catalysts were prepared by incipient wetness impregnation (Cu/SiO2-I), precipitation?deposition(Cu/SiO2-PD) and co-precipitation (CuMgAl, CuZnAl and Cu-Cr) methods. CuMgAl, CuZnAl and Cu/SiO2-PD showed higher Cu dispersion and H2 chemisorption capacity than Cu-Cr and Cu/SiO2-I. The selectivity to furfuryl alcohol, at 383 K and 10 bar, using 2-propanol as solvent, was 100% in all of the cases. The pattern for the hydrogenation rate per gram of Cu was: CuMgAl > Cu/SiO2-PD > CuZnAl > Cu-Cr > Cu/SiO2-I. Instead, the hydrogenation rate per Cu atom on the surface (TOF) followed the pattern: CuMgAl > Cu-Cr > Cu/SiO2-PD = CuZnAl > Cu/SiO2-I. These are promising results for the future replacement of polluting Cu-Cr industrial catalysts by a Cr-free one. The highest activity of CuMgAl was attributed to an intimate and effective interaction between Cu0 atoms and Mg2+ cations in a spinel-like matrix. Additional catalytic tests, varying reactant initial concentration and temperature, were performed with CuMgAl catalyst. A negative reaction order (n=−1) respect to furfural and a high apparent activation energy (Ea=127 KJ mol−1) were estimated, indicating a very strong adsorption of furfural on metal copper surface.